Brexit: Challenges for Universities in Hard Times - Marginson, Simon (International Higher Education, 2017)
The UK has voted to leave the EU primarily because of opposition to migration. Free movement from EU countries into UK will end with ‘Brexit’ in 2019 and international student numbers will be cut sharply. Universities face a substantial decline in international student revenues—initially among non-EU students—and lose participation in EU collaborative research schemes which generate £1 billion year in UK research activity.